Strength Characteristics of GGBS and Steel Slag based Binary Mix Concrete - K.Siddhartha, K; Bhuvaneshwari, P; Raja Mohan.K, Saravana (International Journal of Engineering and Technology, 2018)
The objective of this study is to experimentally study the effect of partial replacement of Portland cement and fine aggregate by the industrial wastes ground granulated blast furnace slag (GGBS) and steel slag (SS) respectively, on the various strength parameters of concrete. Totally 9 mixes were proposed according to ACI standards, with varying replacements of cement with 40%, 50% and 60% of GGBS and varying replacement of fine aggregate with steel slag by 10%, 20% and 30% weight of concrete. The compressive strength using cubes of size 100 mm x 100 mm x 100 mm and splitting tensile strength using cylinder of size 100 mm x 200 mm were found out for curing periods of 14 and 28 days respectively for all the mixes. Results were then compared with conventional concrete and the optimum replacement percentage of GGBS and steel slag is reported.Â Â
Keywords: Ground granulated blast furnace slag; Steel slag; Compressive strength; Tensile strength.